Differences in Students Emotional Intellegence Based on Gender - Meirizka Liyani Putri; Yusri Yusri (Universitas Negeri Padang, 2021)
Someone who has good emotional intelligence will be able to recognize and manage their own emotions, be able to motivate themselves, recognize other people's emotions and be able to build good relationships with others. Every individual has different emotional intelligence depending on the factors that affect emotional intelligence itself. One of the factors that affect emotional intelligence is gender. This study aims to determine how the differences in students' emotional intelligence based on gender. This research is a type of comparative descriptive research, with a research sample of 282 students of SMA Negeri 1 Padang who were registered in the 2020/2021 academic year, divided into 123 male students and 159 female students. The results of this study are (1) the emotional intelligence of male students is in the medium category, (2) the emotional intelligence of female students is in the medium category, and (3) there is no significant difference between the emotional intelligence of male students and female students in SMA Negeri 1 Padang.